Pravastatin reduces plasma levels of extracellular vesicles in pregnancies at high risk of term preeclampsia - Santoyo, Jean Michell; Noguera, José Antonio; Avilés, Francisco; Hernández-Caselles, Trinidad; de Paco-Matallana, Catalina; Delgado, Juan Luis; Cuevas, Santiago; Llinás, M. Teresa; Hernández, Isabel (Frontiers in Pharmacology, 2023)
Introduction: Elevated plasma levels of extracellular vesicles have been associated with impaired placentation, angiogenesis imbalance, intravascular inflammation, and endothelial dysfunction in women with preeclampsia, thus suggesting that circulating vesicles may be a good therapeutic target for the treatment of the disease. Recently, statins have been considered a potential treatment for the prevention of preeclampsia because of their pleiotropic effects, including the improvement of endothelial dysfunction and inhibition of inflammatory responses. However, the effects of these drugs on circulating vesicles concentration in women at risk of preeclampsia have not been established. Herein, we aimed to assess the effects of pravastatin on circulating extracellular vesicle generation in women at high risk of term preeclampsia. Methods: In a sample of 68 singleton pregnant women participating in the multicenter, double-blind, placebo-controlled STATIN trial (Nº EducraCT 2016-005206-19 ISRCTN), 35 women received a placebo and 33 women received a 20 mg/day dose of pravastatin for approximately 3 weeks (from 35 to 37 weeks of gestation until delivery). Large extracellular vesicles were characterized and quantified by flow cytometry using annexin V and cell-specific antibodies directed against platelet, endothelial, leukocyte, and syncytiotrophoblast cell surface markers. Results: In women who received the placebo, a significant increase in the plasma levels of large extracellular vesicles from platelets (34%, p < 0.01), leukocytes (33%, p < 0.01), monocytes (60%, p < 0.01), endothelial cells (40%, p < 0.05), and syncytiotrophoblast cells (22%, p < 0.05) were observed. However, treatment with pravastatin significantly reduced the plasma levels of large extracellular vesicles from platelets (42%, p < 0.001), leukocytes (25%, p < 0.001), monocytes (61%, p < 0.001), endothelial cells (69%, p < 0.001), activated endothelial cells (55%, p < 0.001), and syncytiotrophoblast cells (44%, p < 0.001). Discussion: These results indicate that pravastatin reduces the levels of activated cell-derived membrane vesicles from the maternal vasculature, blood, and placental syncytiotrophoblast of women at high risk of term preeclampsia, suggesting that this statin may be beneficial in reducing endothelial dysfunction and pro-inflammatory and pro-coagulatory state characteristics of the disease.